Analisis Kinerja IPAL PT X Jawa Timur dalam Menurunkan Parameter Pencemar Menggunakan Pendekatan Water Quality Index (WQI) - Muchammad Ali Fikri; R Mohammad Alghaf Dienullah (JURNAL WILAYAH, KOTA DAN LINGKUNGAN BERKELANJUTAN, 2025)
The plastic recycling industry generates wastewater that poses a potential threat to aquatic environments if not managed optimally. Performance evaluation of Wastewater Treatment Plants (WWTP) is typically conducted partially by comparing outlet parameters against effluent standards, often failing to depict water quality conditions holistically. Therefore, this study employs the Water Quality Index (WQI) approach using the Canadian Council of Ministers of the Environment (CCME) method to evaluate the performance of PT X's WWTP in East Java. This research utilized secondary data from inlet and outlet wastewater quality tests over 23 months (January 2024–November 2025), covering 10 parameters. Analysis was conducted by calculating removal efficiency and determining factors F1 (scope), F2 (frequency), and F3 (amplitude) as the basis for the WQI-CCME calculation. The results indicate that the WWTP achieved high efficiency (>80%) in reducing dominant parameters such as TSS, TDS, BOD, and COD. However, violations of effluent standards were still observed in certain parameters. The obtained WQI-CCME value was 69,30, categorized as "Fair" with a moderate level of violation. These findings demonstrate that although the WWTP meets regulatory standards, the WQI-CCME approach provides a more comprehensive assessment of performance. Optimization of advanced treatment units is recommended to improve effluent quality and sustainable WWTP performance.